Optimization of Hydraulic Servo Parameter for Semi-Solid Machine using Aerotech A3200 - Fiqri Ibrahim Amien; Danny M Gandana; Nasril Nasril; Dwi Astharini; Ahmad Husin Lubis (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2018)
Abstract – Hydraulics machines are important parts in semi solid metal forging machine, to form the workpiece by pressing. Semi-solid machine positioning movements are required to have a high accuration, to get the high accuracy of the movement system a servo hydraulic control is added ,which consist of servo valve and digital controller (Aerotech A3200). The digital control parameters (kpos, kp, ki) are used to enhanced the hydraulic movement. To get the effect of the control parameters of the plant (hydraulic servo), a mathematical approach is used for simulation in matlab. In this research, study was done by optimize kp and ki parameters of the control system. Prior to the optimization, simulation was conducted using matlab. Where the simulated testing is using the input unit (step) and frequency (bode) to predict the circumstances that occurred to the plan which is then compared with experimental results. a step response was simulated in matlab to analyze the error of the hydraulic system. Having obtained the minimum error from adjusting kp and ki in matlab, a trend graphic error was used as a guideline to adjust parameter in actual system. The last step is to implement and adjust kp/ki in actual system and measure the real position error.Based on this research, it concluded that the error before adjustment are 0.6118-1.2642 mm for autotune  parameter kp 3500000, ki 50000. The result of average error in this experiments after adjustment are 0.017-0.166 mm for parameter kp 250000, ki 10000. Keywords - Hydraulic Servo, Aerotech A3200, Step response, Bode plot, Semi-Solid Machine.